KAJIAN STILISTIKA DALAM TEKS AL-MUTAWASSIMĪN SEBAGAI BAHAN PEMBELAJARAN MATA KULIAH WAJIB STILISTIKA - Dhimas Muhammad Yasin (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
This article discusses stylistic in Al-Mutawassimīn text, a Malay text  manuscript. This study used qualitative descriptive design.  The manuscript was evaluated its stylistics aspects and its characteristics were elaborated.  The findings of analysis indicate that characteristics stylistic Al-Mutawassimīn text use a style of a hallmark of a genre of religious literature.  The styles of genre were identified thorugh vocabulary, phrases, syntax, rhetoric or language means rhetorical and figurative language.  Stylistics of Al-Mutawassimin are five kinds: (1) kinds of vocabulary are  Indonesian, Arabic, Java, and some phrases in Arabic; (2) syntactics are in the form of the use of the conjunction "and" and "then"; (3) rhetoric means consist of polisindeton, (4)  euphemism and litotes are used; and (5) figurative languages such as simile are present.